FAKTOR PENGHAMBAT KEMAMPUAN SISWA SMP DALAM MEMBACA AL-QURAN - Budi Nurdiana; Ane Zunnatul Mafruhah; Hasbiyallah Hasbiyallah; Ida Farida Ch (Almarhalah, 2022)
ABSTRACTReading the Qur'an is an obligation for Muslims and Muslim women to be studied because the Qur'an is the foundation in understanding Islamic teachings. The most basic thing for students is to be able to read the Koran properly and correctly in accordance with the legal rules of reading the Koran such as recitation and makhorijul letters. However, there are still students who have difficulty reading the Qur'an. Factors that cause students' low ability to read the Qur'an are internal factors from students who are lazy to recite the Koran because they mostly play gadgets and external factors are motivation from weak parents. This study aims to analyze the factors that hinder the ability to read the Koran in grade VII in one of the junior high schools in Garut city. The method used in this research is descriptive quantitative by using the Koran reading test as the research instrument. the test results of the ability to read the Qur'an from 40 students who are included in the low category as many as 4 people. Therefore, the role of educators, parents, and the environment will greatly affect the motivation of students in reading the Qur'an.Keyword: Reading the Quran, students, inhibiting factor